Attitudes Toward Inclusive Education: An Exploration of the Interaction Between Teachers’ Status and Students’ Type of Disability Within the French Context - Jury, Mickaël; Perrin, Anne-Laure; Rohmer, Odile; Desombre, Caroline (Frontiers in Education, 2021)
The positive attitudes of teachers toward inclusive education appear to be necessary to successfully implement this policy. The present research, conducted within the French context, seeks to replicate the previous findings regarding students’ type of disability or teachers’ status and extend them by specifically examining the interaction between these two variables. We notably hypothesized that (1) teachers’ attitudes toward inclusive education will be the least positive for students with autism spectrum disorder (ASD), in comparison with students with cognitive disorder (CD) and students with motor impairment (MI); (2) special education teachers will have more positive attitudes than general teachers; and more importantly (3) special education teachers, in comparison with general teachers, would be less likely to express distinct attitudes depending on the students’ type of disability. An online questionnaire was completed by 311 teachers. The results replicated the previous findings by showing that teachers’ attitudes were more favorable toward students with MI than students with CD or students with ASD. In addition, taking into account teachers’ status, the results showed that if special education teachers had more positive attitudes than general teachers, they, however, expressed less favorable attitudes toward the inclusion of students with ASD in comparison with those with other types of disabilities. These results are notably discussed regarding the lay beliefs associated with students with ASD and the influence of training.